Priority policies and guidelines for research in the microbiological area. - F. Lazo, Ramón (Revista Universidad de Guayaquil, 1990)
Having proposed as one of the main objectives of the "First National Meeting of Researchers in the Technical Area", to propose policies and priority lines of technical research in the context of regional and national development, I considered it necessary to focus on the importance of research in the Microbiological Area. With this purpose I had to analyze, mainly, the small achievements obtained over the years. This situation has undergone a notable change since when the National Council of Universities and Polytechnic Schools (CONUEP) became the Governing Body for research in the country's Universities. The Microbiological Area is made up of a multidisciplinary group, increasingly diversified, mainly the Health Team, and that is why, wishing to contribute to the technological development of the country, I point out the existing concerns and responsibilities.